2013
DOI: 10.1002/j.2168-0159.2013.tb06273.x
|View full text |Cite
|
Sign up to set email alerts
|

41.3: Evaluating the Effects of Environmental Illuminance on the Readability of E‐books

Abstract: We carried out experiments to evaluate the readability of reading e-books under staged illuminance conditions (minimum : 10 lx, maximum : 5,000 lx). In the experiments, we conducted subjective evaluations and measured viewing distance. This study found a dependency between readability and illuminance for each device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…However, the evaluations for the backlit LCD were comparable in score to that for the paper text at 1,000 lx illuminance condition, while the best rating at 3,000 lx illuminance was obtained with the paper text. This result was similar to that of our previous study 1) . This study confirmed the superiority of built-in light systems under illuminance conditions of less than 1,000 lx compared to reflective devices, which was also similar to our previous study under illuminance conditions of less than 750 lx 2) .…”
Section: Discussionsupporting
confidence: 93%
“…However, the evaluations for the backlit LCD were comparable in score to that for the paper text at 1,000 lx illuminance condition, while the best rating at 3,000 lx illuminance was obtained with the paper text. This result was similar to that of our previous study 1) . This study confirmed the superiority of built-in light systems under illuminance conditions of less than 1,000 lx compared to reflective devices, which was also similar to our previous study under illuminance conditions of less than 750 lx 2) .…”
Section: Discussionsupporting
confidence: 93%
“…For all contrast ratios, the subjective evaluation of paper was higher than that of the ILU-EPD. These results were consistent with previous experiments [8]. For the ILU-EPD and EPD, the subjective evaluations at the High level were higher than that of the Medium level.…”
Section: Exp 3 (Character Size)supporting
confidence: 93%
“…In contrast, most of tablet devices have a backlit LCD. Out previous study showed that under conditions of low illuminance, the readability of the e-paper is poor [1]. However, a built-in light system would improve the readability of the e-paper under low illuminance conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%